2013
DOI: 10.1002/2013ja019144
|View full text |Cite
|
Sign up to set email alerts
|

An observational and theoretical study of the longitudinal variation in neutral temperature induced by aurora heating in the lower thermosphere

Abstract: [1] In this paper, observations by thermosphere, ionosphere, mesosphere energetics and dynamics/Sounding of the Atmosphere using Broadband Emission Radiometry from 2002 to 2012 and by Envisat/Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) from 2008 to 2009 are used to study the longitudinal structure of temperature in the lower thermosphere. In order to remove the longitudinal structure induced by tides, diurnally averaged SABER temperatures are used. For MIPAS data, we use averaged temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…The operationally retrieved parameters (T k , O 3 , and several volume emission rates) are routinely used in dynamical and trend studies e.g. Gao et al (2010), Xu et al (2013), Smith et al (2013), Goldberg et al (2013). The absolute values of the T k profiles are not crucial in these cases; only its precision is important.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The operationally retrieved parameters (T k , O 3 , and several volume emission rates) are routinely used in dynamical and trend studies e.g. Gao et al (2010), Xu et al (2013), Smith et al (2013), Goldberg et al (2013). The absolute values of the T k profiles are not crucial in these cases; only its precision is important.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, Xu et al (2013) showed longitudinal variations of the thermospheric temperature from satellite observations with SABER and Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) and simulations with TIE-GCM. Their simulations clarified that auroral heating would cause the observed longitudinal temperature variations.…”
Section: Mlt Regionmentioning
confidence: 99%
“…One process is the direct effect on the temperature and dynamics. The geomagnetic storm is followed in the atmosphere by ionization, excitation, Joule heating and dissociation processes (Lastovicka, 1996;Xu et al, 2013). There is some evidence of the upper atmosphere temperature change during EPP.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence of the upper atmosphere temperature change during EPP. Xu et al (2013) investigated the longitudinal temperature structure in the lower thermosphere using the SABER/TIMED and MIPAS/Envisat (Michelson Interferometer for Passive Atmospheric Sounding) data obtained from 2008 to 2009. The study of these satellite measurements revealed that the maximum of the diurnally averaged temperature in the lower thermosphere is near the longitude of the magnetic pole in both the Northern Hemisphere and the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%